C-CNTF / HfC-SiC ceramic-based composite material and preparation method thereof

Through shear dispersion technology and vacuum-pressurized immersion method, combined with the suture technology of carbon nanotube fibers, the problems of unstable slurry and insufficient thermal conductivity in the preparation of Hf-based ultra-high temperature ceramic matrix composite materials are solved, achieving high efficiency Thermal conductivity regulation and material performance improvement.

CN119430973AActive Publication Date: 2025-02-14AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411683983.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The prior art has problems such as carbon thermal reduction damage to the fibers and unstable slurry, resulting in the inability to immerse into the prefabricated body evenly when preparing the Hf-based ultra-high temperature ceramic matrix composite.

Method used

The new shear dispersion technology and the hierarchical vacuum-pressurized layer-by-layer impregnation method are adopted to achieve uniform and stable dispersion of solid slurry and particle size control, and Z-directional suture of continuous carbon nanotube fibers is carried out to regulate the thermal conductivity of composite materials in a directional manner. .

Benefits of technology

The uniform and dense distribution of the slurry is achieved, the thermal conductivity and ablation resistance of the material are improved, the stationary temperature is reduced, and the mechanical properties of the composite material are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a C-CNTF / HfC-SiC ceramic matrix composite material and a preparation method thereof. The preparation method comprises the following steps: carrying out shearing dispersion treatment on HfC powder and optional graphene in a solvent to prepare a slurry dispersion liquid; impregnating fiber cloth by using the slurry dispersion liquid, drying and curing; laminating the fiber cloth, and sewing the fiber cloth in the Z direction by using continuous carbon nanotube fibers; dipping with HfC slurry, drying and curing; and dipping by using a polycarbosilane precursor, and then curing and cracking to obtain the ceramic-based composite material. The invention also relates to the composite material prepared by the method. According to the method, solid slurry with stable dispersibility is obtained by graphene-assisted shearing dispersion; uniform impregnation of the slurry is realized by adopting a multi-stage vacuum-pressure impregnation mode; directional regulation and control of the heat conductivity are realized through Z-direction sewing of the carbon nanotube fibers; finally, the composite material with excellent mechanical property and thermal protection property is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic-based composite material preparation, and specifically to a C-CNTF / HfC-SiC ceramic-based composite material and a preparation method thereof. Background Art

[0002] In recent years, in order to address the problem of ultra-high-speed flight aerodynamic heating causing rapid heating of the leading edge, nose cone and other parts of high-speed aircraft, there is an urgent need to develop ultra-high temperature ceramic-based composite materials with both excellent mechanical properties and anti-oxidation and ablation properties.

[0003] At present, the research work carried out by researchers on continuous carbon fiber reinforced ultra-high temperature ceramic matrix composites (C / UHTCs) involves preparation process, material system and failure mechanism under extreme environment. These research works mainly focus on C / ZrC, C / ZrC-SiC, C / ZrB 2 -SiC and other zirconium (Zr) based ultra-high temperature ceramic matrix composite materials.

[0004] However, compared with Zr-based ultra-high temperature ceramics, hafnium carbide (HfC) and hafnium boride (HfB 2 ) has a higher melting point. Among them, hafnium oxide (HfO 2 ) has a lower oxygen diffusion rate and vapor pressure, which enables it to maintain long-term stability and good oxygen isolation performance in extreme environments. Therefore, hafnium (Hf)-based ultra-high temperature ceramic-based composite materials with higher temperature resistance are expected to become important thermal protection materials for aircraft thermal structural components that can withstand 2500-3000℃.

[0005] At present, the commonly used processes for preparing Hf-based ultra-high temperature ceramic-based composites, such as precursor infiltration and pyrolysis (PIP), metal reactive infiltration (RMI), chemical vapor infiltration (CVI) and slurry infiltration (SI), all have problems such as carbon thermal reduction damaging the fibers and unstable slurry that cannot be evenly infiltrated into the preform.

[0006] In order to solve the above technical problems, the inventors innovatively use a new type of shear dispersion technology to achieve uniform and stable dispersion of solid slurry and particle size control. A graded vacuum-pressurized layer-by-layer impregnation method is used to achieve uniform filling of slurry between and inside fiber bundles.

[0007] In addition, in order to further improve the thermal protection performance of the material, the present invention adopts a strategy of combining efficient thermal conductivity with high temperature heat resistance. As a typical representative of new high-performance fibers, the one-dimensional macroscopic material composed of oriented carbon nanotubes, carbon nanotube fiber (CNTF), exhibits excellent properties such as high strength, high toughness, and high thermal conductivity. Compared with traditional metal or alloy materials, carbon nanotube fiber-reinforced composite materials have higher specific performance (specific strength and specific modulus).

[0008] The present invention utilizes the excellent properties of carbon nanotubes, and while improving the heat resistance of the material, uses continuous carbon nanotube fibers for stitching to directionally improve the thermal conductivity of the material, effectively reduce the stagnation temperature of the material, and improve the material's anti-ablation performance. Summary of the invention

[0009] In view of the problems existing in the prior art such as carbon thermal reduction damaging fibers and slurry instability leading to inability to uniformly immerse into the interior of the preform, the present invention provides a C-CNTF / HfC-SiC ceramic matrix composite material and a preparation method thereof in the first aspect, the method comprising the following steps:

[0010] (1) subjecting HfC powder and optionally graphene to a shear dispersion treatment in a solvent to prepare at least two slurry dispersions having different solid particle sizes;

[0011] (2) impregnating fiber cloth with the slurry dispersion in the order of solid particle size from large to small, drying and solidifying to obtain an impregnated fiber cloth;

[0012] (3) stacking the impregnated fiber cloths and then performing Z-direction stitching using continuous carbon nanotube fibers to obtain a preform structure;

[0013] (4) impregnating the preform structure with HfC slurry, and then drying and curing to obtain a C / HfC green body;

[0014] (5) impregnating the C / HfC body with a polycarbosilane precursor, and then curing and cracking the body to obtain a C-CNTF / HfC-SiC ceramic matrix composite material.

[0015] In a second aspect, the present invention provides a C-CNTF / HfC-SiC ceramic matrix composite material prepared by the method described in the first aspect of the present invention.

[0016] The beneficial effects of the present invention compared with the prior art are as follows:

[0017] (1) The present invention adopts a novel shear dispersion processing technology to achieve efficient dispersion of solid slurry, and at the same time can regulate the particle size of solid particles. In the case where graphene is used to assist shear dispersion, the effective coating of graphene on the particle surface can be used to avoid particle reaggregation, thereby obtaining a solid slurry that can be stored for a long time and maintains dispersion stability.

[0018] (2) The present invention uses a multi-stage vacuum-pressure impregnation method to achieve uniform slurry impregnation inside and between fiber bundles. Submicron large particle slurry is first used to quickly fill the larger pores between fiber bundles to improve the densification efficiency, and then small particle HfC slurry is used to further fill the pores inside the fiber bundle, further increasing the slurry impregnation density, reducing the porosity, and improving the mechanical properties of the composite material.

[0019] (3) The present invention uses continuous carbon nanotube fibers to sew in the Z direction to obtain a preform structure, and directionally controls the thermal conductivity of the composite material by adjusting the sew spacing and the number of carbon nanotube strands. In a preferred embodiment using graphene, the overall thermal conductivity of the material can be assisted in controlling by adjusting the graphene content in the slurry. The preparation of C-CNTF / HfC-SiC ceramic-based composite materials with directionally controlled thermal conductivity is achieved by combining slurry impregnation with a precursor impregnation and cracking process. The present invention uses a strategy that combines efficient thermal conductivity with high-temperature heat resistance to further enhance the thermal protection performance of the material. DETAILED DESCRIPTION

[0020] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material with directional control of thermal conductivity by multi-stage impregnation of graphene-assisted slurry dispersion, the method comprising the following steps:

[0021] (1) subjecting HfC powder and optionally graphene to a shear dispersion treatment in a solvent to prepare at least two slurry dispersions having different solid particle sizes;

[0022] (2) impregnating fiber cloth with the slurry dispersion in the order of solid particle size from large to small, drying and solidifying to obtain an impregnated fiber cloth;

[0023] (3) stacking the impregnated fiber cloths and then performing Z-direction stitching using continuous carbon nanotube fibers to obtain a preform structure;

[0024] (4) impregnating the preform structure with HfC slurry, and then drying and curing to obtain a C / HfC green body;

[0025] (5) impregnating the C / HfC body with a polycarbosilane precursor, and then curing and cracking the body to obtain a C-CNTF / HfC-SiC ceramic matrix composite material.

[0026] The preferred implementation of the method of the present invention will be further described below in steps.

[0027] Step (1)

[0028] In step (1), HfC powder is subjected to a shear dispersion treatment in a solvent to prepare at least two slurry dispersions having different solid particle sizes.

[0029] In some preferred embodiments, when preparing at least two slurry dispersions with different solid particle sizes, graphene (graphene as an optional added component or a preferred added component) can also be added to assist the shear dispersion process. In this case, it is preferred to firstly perform ultrasonic treatment on the graphene dispersion (which can be prepared by adding graphene to the solvent), and then add HfC powder for shear dispersion treatment to prepare at least two slurry dispersions with different solid particle sizes.

[0030] The purpose of the ultrasonic treatment is to improve the surface wettability. The ultrasonic treatment of the present invention is not particularly limited. For example, it can be achieved by using an ultrasonic cell crusher for 20 min to 40 min, such as 30 min.

[0031] The present invention has no particular limitation on the initial particle size of graphene, but mainly has a preferred particle size range for the particle size after shear dispersion treatment. For example, for graphene, its initial particle size can be 0.5 μm to 1 μm, such as 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0 μm.

[0032] The present invention also has no particular limitation on the initial particle size of the added HfC powder, because the subsequent shearing process will make the particle size of the HfC powder within the expected solid particle size range. For example, the initial particle size of the HfC powder can be the same as the initial particle size of the graphene, or it can be different, for example, less than 10 μm.

[0033] In addition, preferably, the solvent in the graphene dispersion is ethanol.

[0034] In addition, preferably, the HfC in the slurry dispersion is 15 volume % to 25 volume %, for example, 20 volume %.

[0035] It is also preferred that the graphene in the slurry dispersion is 0 volume % to 45 volume %, for example, 1, 5, 10, 15, 20, 25, 30, 35, 40 or 45 volume %.

[0036] Preferably, the shear dispersion treatment is a vertical liquid particle shear dispersion treatment. In the present invention, "vertical liquid particle shear dispersion treatment" means that the liquid containing particles is oscillated in a vertical direction to generate a predetermined amount of shear force so as to achieve the dispersion of particles in the liquid by means of the shear force. More preferably, the shear force of the shear dispersion treatment is 50N to 100N (for example, 60, 70, 80 or 90N), and the treatment time is 30min to 150min (for example, 60, 90 or 120min). The inventors found that the solid particles oscillate in the vertical direction in the liquid, and the shearing action generated between the particles and between the particles and the solvent molecules can efficiently disperse the solid particles, and realize the efficient attachment of graphene, and obtain a slurry dispersion liquid with very stable dispersion of solid particles. The conventional dispersion method (such as ball milling) cannot achieve good dispersion of HfC powder, and the effective coating of graphene on the surface of HfC powder cannot be achieved when graphene is used to assist dispersion.

[0037] In this step, small-sized graphene is combined with shear dispersion treatment (preferably vertical liquid particle shear dispersion treatment) to achieve rapid and uniform dispersion of particles in the HfC slurry. In the case of using graphene, graphene can also be uniformly coated on the surface of the particles. The particle size can be controlled by adjusting the shear force and duration of the treatment, especially when using small-sized graphene surface coating, it can more effectively prevent the particles from reaggregating in the solution, prolong the storage time of the slurry, and improve the stability of the slurry.

[0038] Step (2)

[0039] In step (2), the fiber cloth is impregnated with the slurry dispersion in the order of solid particle size from large to small, and dried and solidified to obtain an impregnated fiber cloth.

[0040] Preferably, the fiber cloth is a carbon fiber cloth or a carbon nanotube fiber cloth, preferably a single-layer fiber cloth, and more preferably a single-layer plain-weave fiber cloth.

[0041] More preferably, the solid particle size of the at least two slurry dispersions is independently in the range of 200 nm to 2 μm. In some preferred embodiments, the solid particle size of the slurry dispersion with a larger solid particle size is 1.5 to 2 μm, while the solid particle size of the slurry dispersion with a smaller solid particle size is 0.2 to 1.2 μm.

[0042] In some preferred embodiments, the at least two slurry dispersions include a first slurry dispersion having a solid particle size of 1.5 to 2 μm and a second slurry dispersion having a solid particle size of 0.8 to 1.2 μm.

[0043] In other preferred embodiments, the at least two slurry dispersions include a first slurry dispersion with a solid particle size of 1.5 to 2 μm, a second slurry dispersion with a solid particle size of 0.8 to 1.2 μm, and a third slurry dispersion with a solid particle size of 0.2-0.5 μm.

[0044] Of course, more slurry dispersions with different solid particle sizes can also be prepared and then used in order of solid particle size from large to small.

[0045] In some preferred embodiments, the at least two slurry dispersions may include a first slurry dispersion having a solid particle size of 1.5 μm to 2 μm, a second slurry dispersion having a solid particle size of 0.8 μm to 1.2 μm, and a third slurry dispersion having a solid particle size of 200 nm to 500 nm.

[0046] More preferably, the impregnation includes vacuum impregnation and pressure impregnation, and the vacuum impregnation is performed first and then the pressure impregnation.

[0047] The present invention has no particular limitation on the vacuum conditions, as long as sufficient impregnation can be achieved. For example, the vacuum degree of the vacuum impregnation can be 10 -3 Pa, the immersion time can be 5 to 10 hours (for example, 6, 7, 8 or 9 hours); the pressure of the pressurized immersion is 15 MPa to 25 MPa (for example, 20 MPa), and the immersion time is 2 hours to 4 hours (for example, 3 hours).

[0048] In addition, preferably, the drying and curing temperature is 180° C. to 220° C. (eg, 200° C.) and the time is 3 hours to 5 hours (eg, 4 hours).

[0049] It is also preferred that the impregnation and drying and curing of each of the at least two slurry dispersions can be independently repeated 2 to 4 times, for example 3 times. For example, the slurry dispersion with the largest solid particle size can be impregnated first, then dried and cured, and repeated 2 to 4 times; then the slurry dispersion with the second largest solid particle size can be impregnated, then dried and cured, and independently repeated 2 to 4 times; then the slurry dispersion with the smaller solid particle size can be impregnated, then dried and cured, and independently repeated 2 to 4 times. That is, the number of repetitions of impregnation and drying and curing of each slurry dispersion can be the same or different.

[0050] In some more specific embodiments, the single-layer carbon fiber cloth may be first subjected to a multi-stage impregnation treatment with HfC slurry. For example, the single-layer carbon fiber cloth may be first subjected to vacuum-pressure impregnation with 0.8 μm to 1 μm HfC slurry to fill the pores between the fiber bundles, the vacuum impregnation time is 5 h to 10 h, the pressure is 20 MPa for impregnation for 2 h to 4 h, and the drying and curing is performed at 200 ° C for 4 h. Then, the internal pores of the fiber bundle are filled with 200 nm to 500 nm HfC slurry, and the treatment conditions are the same as above. This process may be repeated 2 to 4 times.

[0051] This step adopts the mode of multi-stage vacuum-pressure impregnation to realize the uniform impregnation of slurry inside and between fiber bundles. Submicron large particle slurry can be used to quickly fill the larger pores between fiber bundles first, improve the densification efficiency, and then use small particle HfC slurry to further fill the internal pores of fiber bundles, further improve the slurry impregnation density, reduce porosity, and improve the mechanical properties of composite materials. In the case of using graphene, the graphene in the slurry dispersion can also be used to assist thermal conductivity improvement. Wherein, graphene includes graphene coated on the HfC surface and graphene not coated on the HfC surface, the latter can be filled in the fiber interior or coated on the fiber surface, so as to assist thermal conductivity improvement.

[0052] Step (3)

[0053] In step (3), the impregnated carbon fiber cloths are stacked and then sutured in the Z direction using continuous carbon nanotube fibers to obtain a preform structure.

[0054] Preferably, the tensile strength of the continuous carbon nanotube fiber is greater than 3 GPa, the diameter of the single filament is 10 μm to 15 μm (for example, 11, 12, 13 or 14 μm), the room temperature thermal conductivity is 400 to 600 W / m·K (for example, 450, 500 or 550 W / m·K), and the elongation at break is 4% to 6% (for example, 5%). Such continuous carbon nanotube fibers have excellent toughness and can further improve the mechanical properties of the resulting composite material.

[0055] More preferably, the linear density of the continuous carbon nanotube fibers is 50 tex to 70 tex.

[0056] More preferably, the number of the suture strands is 1 to 5 (eg, 2, 3 or 4).

[0057] More preferably, the suture spacing is 1.5 mm to 4.0 mm (e.g., 2.0, 2.5, 3.0 or 3.5 mm). More specific examples of suture spacing may be, for example, 1.5 mm×1.5 mm, 2 mm×2 mm, 2.5 mm×2.5 mm, 3 mm×3 mm, 3.5 mm×3.5 mm, 4 mm×4 mm.

[0058] In the present invention, the number of the stacked layers is not particularly limited and can be increased or decreased as appropriate according to actual needs. In some preferred embodiments, the number of the stacked layers can be 5 to 20 layers (for example, 10 or 15 layers).

[0059] In this step, the impregnated single-layer fiber cloth is stacked and then sutured in the Z direction using continuous carbon nanotube fiber (CNTF) to obtain a preform structure. Moreover, by adjusting the suture spacing and the number of strands of the continuous carbon nanotube fiber, the thermal conductivity of the composite material can be directionally adjusted.

[0060] Step (4)

[0061] In step (4), the preform structure is impregnated with HfC slurry (this is the last HfC slurry impregnation after stitching), and then dried and cured to obtain a C / HfC green body.

[0062] Preferably, the particle size of the HfC slurry is 100 nm to 300 nm (eg, 200 nm).

[0063] More preferably, the solvent of the HfC slurry may be ethanol.

[0064] More preferably, the HfC in the HfC slurry may be 15 volume % to 25 volume % (eg, 20 volume %).

[0065] More preferably, the drying and curing temperature is 200° C. to 400° C., and the curing time is 2 hours to 4 hours.

[0066] Step (5)

[0067] In step (5), the C / HfC body is impregnated with a polycarbosilane precursor, and then cured and cracked to obtain a C-CNTF / HfC-SiC ceramic matrix composite material.

[0068] Preferably, the curing temperature (or cross-linking temperature) of the polycarbosilane precursor is 200 to 400°C (for example, 300°C), the curing time is 100 to 360 min (for example, 150, 200, 250, 300 or 350 min), and the pyrolysis temperature is 800°C to 1000°C (for example, 900°C). The immersion pyrolysis can be repeated until the mass increase is less than 1%.

[0069] In this step, the green body is densified by using a polycarbosilane impregnation-pyrolysis process. The preparation of C-CNTF / HfC-SiC ceramic-based composite materials with directional control of thermal conductivity is achieved by combining slurry impregnation with a precursor impregnation-pyrolysis process.

[0070] The present invention proposes a new type of shear dispersion technology to disperse solid slurry with high efficiency, so as to achieve the regulation of the particle size of solid particles. When graphene is used to assist shear dispersion, effective coating of graphene on the surface of particles can be achieved. Through the technical means of graded vacuum-pressure layer-by-layer impregnation, effective filling between fiber bundles and inside fiber bundles can be achieved. The present invention also uses carbon nanotube fibers to construct heat conduction pathways to achieve directional regulation of the thermal conductivity of composite materials. The present invention further combines the precursor impregnation cracking and densification process to prepare a new type of high-temperature resistant and ablation-resistant ceramic-based composite material with directional regulation of thermal conductivity. The composite material not only has high thermal conductivity, but also its mechanical and antioxidant properties are significantly improved.

[0071] In addition, the overall processing temperature of the present invention is relatively low, which avoids the damage of high temperature to the fiber during the preparation of HfC by carbon thermal reduction, and realizes the uniform and stable dispersion of the slurry and the uniform and dense distribution in the fiber. The heat conduction path constructed by carbon nanotube fibers can directionally improve the thermal conductivity of the material, reduce the stagnation temperature, and improve the high temperature resistance and ablation resistance of the material.

[0072] In a second aspect, the present invention provides a C-CNTF / HfC-SiC ceramic matrix composite material prepared by the method described in the first aspect of the present invention.

[0073] Preferably, the content of the Z-direction continuous carbon nanotube fibers in the C-CNTF / HfC-SiC ceramic-based composite material is preferably 5 volume % to 15 volume % (eg 10 volume %).

[0074] It is also preferred that the content of graphene in the C-CNTF / HfC-SiC ceramic-based composite material may be 0 volume % to 30 volume % (for example, 1, 5, 10, 15, 20 or 25 volume %), preferably 10 volume % to 30 volume %.

[0075] Example

[0076] The present invention is described in detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only used to illustrate the present invention and do not constitute a limitation of the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources. Unless otherwise specified, all percentages and parts are by weight.

[0077] Example 1

[0078] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and ultrasonically crushed for 30 min to obtain a graphene dispersion. HfC powder (initial particle size less than 10 μm) was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a graphene volume ratio of 30% and a HfC volume ratio of 25%. Specifically, when the shear force of the vertical liquid particle shear dispersion treatment was 50 N and the treatment time was 60 min, a first slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 80 N and the treatment time was 100 min, a second slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 100 N and the treatment time was 150 min, a third slurry dispersion with a solid particle size of 200-500 nm was obtained.

[0079] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-stage impregnation treatment with the HfC slurry dispersion. First, a 1.5-2μm HfC slurry dispersion (i.e., the first slurry dispersion) is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, and the pressure (20MPa) impregnation is performed for 2h. Drying and curing at 200℃ for 4h completes the first-stage impregnation treatment. Then, a 0.8-1.2μm HfC slurry dispersion (i.e., the second slurry dispersion) is used to fill the remaining pores between the fiber bundles. The treatment conditions are the same as the first-stage impregnation to complete the second-stage impregnation treatment. Finally, a 200-500nm slurry dispersion (i.e., the third slurry dispersion) is used for vacuum impregnation to fill the internal voids of the fiber bundle. The vacuum impregnation time is 5 hours, the pressurized (20MPa) impregnation is performed for 4 hours, the curing temperature is 200°C, and the curing time is 4 hours to complete the third level impregnation treatment.

[0080] (3) After the above-mentioned impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3Gpa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 4mm×4mm, the number of strands of the continuous carbon nanotube fiber is 2, and the linear density is 60tex; the content of the continuous carbon nanotube fiber in the Z direction (hereinafter referred to as "Z-direction fiber content") is 5%.

[0081] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300nm, solvent is ethanol) is carried out, the vacuum impregnation time is 8h, the pressurized (20MPa) impregnation time is 4h, and the C / HfC blank is dried and cured at 200℃ for 4h to obtain the C / HfC blank.

[0082] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and cracking are repeated until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 20% and the volume content of graphene is 24%).

[0083] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 297 MPa, and the Z-direction thermal conductivity is 50 W / m·K.

[0084] Example 2

[0085] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and ultrasonically crushed for 30 min to obtain a graphene dispersion. HfC powder was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a volume ratio of 30% graphene and a volume ratio of 25% HfC. Specifically, when the shear force of the vertical liquid particle shear dispersion treatment was 50 N and the treatment time was 60 min, a first slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 80 N and the treatment time was 100 min, a second slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 100 N and the treatment time was 150 min, a third slurry dispersion with a solid particle size of 200-500 nm was obtained.

[0086] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-stage impregnation treatment with HfC slurry dispersion. First, a 1.5-2μm HfC slurry dispersion is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, the pressure (20MPa) impregnation is 2h, and it is dried and cured at 200℃ for 4h to complete the first-stage impregnation treatment. Then, a 0.8-1.2μm HfC slurry dispersion is used to fill the remaining pores between the fiber bundles. The treatment conditions are the same as the first-stage impregnation treatment to complete the second-stage impregnation treatment. Finally, a 200-500nm slurry dispersion is used to fill the internal voids of the fiber bundle. The vacuum impregnation time is 5h, the pressure (20MPa) impregnation is 4h, and the drying and curing is 4h at 200℃ to complete the third-stage impregnation treatment. The above three-stage impregnation treatment steps are repeated twice each (ie, the first stage impregnation treatment is repeated twice, then the second stage impregnation treatment is repeated twice, and then the third stage impregnation treatment is repeated twice).

[0087] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 3mm×3mm, the number of continuous carbon nanotube fibers is 3, and the Z-direction fiber content is 10%.

[0088] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300nm, solvent is ethanol) is carried out, the vacuum impregnation time is 8h, the pressurized (20MPa) impregnation is 4h, and the drying and curing is carried out at 200℃ for 4h. This process is repeated twice to obtain a C / HfC blank.

[0089] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and cracking are repeated until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 25% and the volume content of graphene is 30%).

[0090] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 317 MPa, and the Z-direction thermal conductivity is 90 W / m·K.

[0091] Example 3

[0092] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and ultrasonically crushed for 30 minutes to obtain a graphene dispersion. HfC powder was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a volume ratio of 30% graphene and a volume ratio of 25% HfC. Specifically, when the shear force of the vertical liquid particle shear dispersion treatment was 50N and the treatment time was 60 minutes, a slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 80N and the treatment time was 100 minutes, a slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained.

[0093] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a secondary impregnation treatment with HfC slurry. First, a 1.5-2μm HfC slurry dispersion is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, and the pressure (20MPa) impregnation is performed for 2h. Drying and curing at 200℃ for 4h completes the first-stage impregnation treatment. Then, a 0.8-1.2μm HfC slurry dispersion is used to fill the remaining pores between the fiber bundles. The treatment conditions are the same as the first-stage impregnation treatment to complete the second-stage impregnation treatment. The above-mentioned secondary impregnation treatment steps are repeated twice each.

[0094] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 3mm×3mm, the number of continuous carbon nanotube fibers is 3, and the Z-direction fiber content is 10%.

[0095] (4) After stitching, the last HfC slurry impregnation was carried out (the slurry particle size was 100-300 nm, the vacuum impregnation time was 8 h, the pressure (20 MPa) impregnation was 4 h, and the C / HfC body was obtained by drying and curing at 200 °C for 4 h.

[0096] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and cracking are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 15% and the volume content of graphene is 18%).

[0097] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 250 MPa, and the thermal conductivity in the Z direction is 80 W / m·K.

[0098] Example 4

[0099] (1) Preparation of HfC slurry: HfC powder was added to 500 mL of ethanol for vertical liquid particle shear dispersion to obtain a slurry dispersion with a HfC volume ratio of 25%. Specifically, when the vertical liquid particle shear dispersion treatment shear force was 50 N and the treatment time was 60 min, a slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the vertical liquid particle shear dispersion treatment shear force was 80 N and the treatment time was 100 min, a slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained; when the vertical liquid particle shear dispersion treatment shear force was 100 N and the treatment time was 150 min, a slurry dispersion with a solid particle size of 200-500 nm was obtained.

[0100] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-stage impregnation treatment with a HfC slurry dispersion. First, a 1.5-2μm HfC slurry dispersion is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 2h, and the first-stage impregnation treatment is completed at 200℃ for 4h. Then, the remaining pores between the fiber bundles are filled with a 0.8-1.2μm HfC slurry dispersion. The treatment conditions are the same as the first-stage impregnation treatment to complete the second-stage impregnation treatment. Finally, a 200-500nm slurry dispersion is used to fill the internal voids of the fiber bundle. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 4h, and the third-stage impregnation treatment is completed at 200℃. Repeat the steps twice.

[0101] (3) After the impregnated single-layer fiber cloth is pressed and stacked, continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, the elongation at break is 4%, and it has excellent toughness. The stitching spacing is 3mm×3mm, the number of continuous carbon nanotube fibers is 3, and the Z-direction fiber content is 10% by volume.

[0102] (4) After suturing, the last HfC slurry impregnation is carried out, the slurry particle size is 100-300nm, the vacuum impregnation time is 8h, the pressure is 20MPa, the impregnation is carried out for 4h, and the drying and curing is carried out at 200℃ for 4h. This is repeated twice to obtain a C / HfC green body.

[0103] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and cracking are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 25% and the volume content of graphene is 0%).

[0104] (6) Mechanical properties and thermal conductivity tests: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested, and the flexural strength was 307 MPa and the Z-direction thermal conductivity was 65 W / m·K.

[0105] Example 5

[0106] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and ultrasonically crushed for 30 min to obtain a graphene dispersion. HfC powder was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a volume ratio of 30% graphene and a volume ratio of 25% HfC. Specifically, when the shear force of the vertical liquid particle shear dispersion treatment was 50 N and the treatment time was 60 min, a slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 80 N and the treatment time was 100 min, a slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 100 N and the treatment time was 150 min, a slurry dispersion with a solid particle size of 200-500 nm was obtained.

[0107] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-stage impregnation treatment with a HfC slurry dispersion. First, a 1.5-2μm HfC slurry dispersion is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 2h, and the first-stage impregnation treatment is completed at 200℃ for 4h. Then, the remaining pores between the fiber bundles are filled with a 0.8-1.2μm HfC slurry dispersion. The treatment conditions are the same as the first-stage impregnation treatment to complete the second-stage impregnation treatment. Finally, a 200-500nm slurry dispersion is used to fill the internal voids of the fiber bundle. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 4h, and the third-stage impregnation treatment is completed at 200℃. Repeat the above three-stage impregnation treatment steps twice.

[0108] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 2mm×2mm, the number of continuous carbon nanotube fibers is 5, and the Z-direction fiber content is 15%.

[0109] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300 nm) is carried out. The vacuum impregnation time is 8 hours, and the pressure (20 MPa) impregnation is 4 hours. Drying and curing at 200°C for 4 hours is repeated twice to obtain a C / HfC blank.

[0110] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and crazing are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 25% and the volume content of graphene is 30%).

[0111] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 330 MPa, and the Z-direction thermal conductivity is 120 W / m·K.

[0112] Example 6

[0113] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and subjected to ultrasonic grinding for 30 min to obtain a graphene dispersion. HfC powder was added to the graphene dispersion and mixed by ball milling to obtain a slurry dispersion with a solid particle size of 1-1.2 μm. The volume ratio of graphene in the slurry dispersion was 30%, and the volume ratio of HfC was 25%.

[0114] (2) Vacuum-pressure impregnation method for slurry impregnation. A single-layer plain carbon fiber cloth was vacuum-pressure impregnated with a 1-1.2 μm HfC slurry dispersion. The vacuum impregnation time was 5 h, the pressure (20 MPa) impregnation was 2 h, and the drying and curing was performed at 200 ° C for 4 h. The impregnation treatment step was repeated 4 times.

[0115] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 3mm×3mm, the number of continuous carbon nanotube fibers is 3, and the Z-direction fiber content is 10%.

[0116] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300 nm) is carried out, the vacuum impregnation time is 8 h, the pressurized (20 MPa) impregnation is 4 h, and the drying and curing is carried out at 200 ° C for 4 h. This is repeated twice to obtain a C / HfC blank.

[0117] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and crazing are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 12% and the volume content of graphene is 14%).

[0118] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 220 MPa, and the Z-direction thermal conductivity is 70 W / m·K.

[0119] Example 7

[0120] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and ultrasonically crushed for 30 min to obtain a graphene dispersion. HfC powder was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a volume ratio of 30% graphene and a volume ratio of 25% HfC. Specifically, when the shear force of the vertical liquid particle shear dispersion treatment was 50 N and the treatment time was 60 min, a slurry dispersion with a solid particle size of 1.5-2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 80 N and the treatment time was 100 min, a slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained; when the shear force of the vertical liquid particle shear dispersion treatment was 100 N and the treatment time was 150 min, a slurry dispersion with a solid particle size of 200-500 nm was obtained.

[0121] (2) The multi-stage vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-stage impregnation treatment with a HfC slurry dispersion. First, a 1.5-2μm HfC slurry dispersion is used to vacuum-pressure impregnate the single-layer plain carbon fiber cloth to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 2h, and the first-stage impregnation treatment is completed at 200℃ for 4h. Then, the remaining pores between the fiber bundles are filled with a 0.8-1.2μm HfC slurry dispersion. The treatment conditions are the same as the first-stage impregnation treatment to complete the second-stage impregnation treatment. Finally, a 200-500nm slurry dispersion is used to fill the internal voids of the fiber bundle. The vacuum impregnation time is 5h, the pressure (20MPa) is impregnated for 4h, and the third-stage impregnation treatment is completed at 200℃. Repeat the above three-stage impregnation treatment steps twice.

[0122] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), 6k T300 carbon fiber is used for Z-axis stitching to obtain a preform structure.

[0123] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300 nm) is carried out. The vacuum impregnation time is 8 hours, and the pressure (20 MPa) impregnation is 4 hours. Drying and curing at 200°C for 4 hours is repeated twice to obtain a C / HfC blank.

[0124] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and crazing are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 25% and the volume content of graphene is 30%).

[0125] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 290 MPa, and the Z-direction thermal conductivity is 20 W / m·K.

[0126] Example 8

[0127] (1) Preparation of HfC slurry: Small-sized graphene (0.5 μm to 1 μm) was placed in 500 mL of ethanol and subjected to ultrasonic grinding for 30 min to obtain a graphene dispersion. HfC powder was added to the above graphene dispersion for vertical liquid particle shear dispersion to obtain a slurry dispersion with a volume ratio of 30% graphene and a volume ratio of 25% HfC. When the vertical liquid particle shear dispersion treatment shear force was 80 N and the treatment time was 100 min, a slurry dispersion with a solid particle size of 0.8-1.2 μm was obtained.

[0128] (2) The vacuum-pressure impregnation method is used to uniformly impregnate the slurry inside and between the fiber bundles. First, the single-layer plain carbon fiber cloth is subjected to a three-level impregnation treatment with the HfC slurry dispersion. The single-layer plain carbon fiber cloth is vacuum-pressure impregnated with a 0.8-1.2μm HfC slurry dispersion to fill the pores between the fiber bundles. The vacuum impregnation time is 5h, the pressure (20MPa) impregnation is 2h, and it is dried and cured at 200℃ for 4h, and repeated 5 times. Finally, it is impregnated again with a 0.8-1.2μm slurry dispersion, the vacuum impregnation time is 5h, the pressure (20MPa) impregnation is 4h, and the drying and curing is 4h at 200℃.

[0129] (3) After the above impregnated single-layer fiber cloth is pressed and stacked (15 layers), continuous carbon nanotube fiber (CNTF) is used for Z-direction stitching to obtain a preform structure. The tensile strength of the continuous carbon nanotube fiber is greater than 3GPa, the single fiber diameter is 14μm, the room temperature thermal conductivity is 600W / m·K, and the elongation at break is 4%. The stitching spacing is 2mm×2mm, the number of continuous carbon nanotube fibers is 5, and the Z-direction fiber content is 15%.

[0130] (4) After suturing, the final HfC slurry impregnation (slurry particle size is 100-300 nm) is carried out. The vacuum impregnation time is 8 hours, and the pressure (20 MPa) impregnation is 4 hours. Drying and curing at 200°C for 4 hours is repeated twice to obtain a C / HfC blank.

[0131] (5) The green body is densified by a polycarbosilane impregnation-cracking process. The crosslinking temperature of the polycarbosilane precursor is 200°C, the curing time is 240 min, the cracking temperature is 900°C, and the impregnation and crazing are performed until the mass increment is less than 1%, thereby obtaining a C-CNTF / HfC-SiC ceramic matrix composite material (wherein the volume content of HfC is 25% and the volume content of graphene is 30%).

[0132] (6) Mechanical properties and thermal conductivity test: The prepared C-CNTF / HfC-SiC ceramic matrix composite material was tested. The test results are as follows: the flexural strength is 280 MPa, and the thermal conductivity in the Z direction is 110 W / m·K.

[0133] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a C-CNTF / HfC-SiC ceramic matrix composite material, characterized in that: The method comprises the following steps: (1) subjecting HfC powder and optionally graphene to a shear dispersion treatment in a solvent to prepare at least two slurry dispersions having different solid particle sizes; (2) impregnating fiber cloth with the slurry dispersion in the order of solid particle size from large to small, drying and solidifying to obtain an impregnated fiber cloth; (3) stacking the impregnated fiber cloths and then performing Z-direction stitching using continuous carbon nanotube fibers to obtain a preform structure; (4) impregnating the preform structure with nano-scale HfC slurry again, and then drying and curing to obtain a C / HfC body; (5) impregnating the C / HfC body with a polycarbosilane precursor, and then curing and cracking the body to obtain a C-CNTF / HfC-SiC ceramic matrix composite material.

2. The preparation method according to claim 1, characterized in that: In step (1): The HfC in the slurry dispersion is 15 volume % to 25 volume %; and / or The graphene in the slurry dispersion is 0 volume % to 45 volume %.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1): The vertical liquid particle shear dispersion treatment of the shear dispersion treatment; Preferably, the shear force of the shear dispersion treatment is 50N to 100N, and the treatment time is 30min to 150min.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2): The fiber cloth is a carbon fiber cloth or a carbon nanotube fiber cloth, preferably a single-layer fiber cloth, more preferably a single-layer plain-weave fiber cloth. The solid particle size of the at least two slurry dispersions is 200 nm to 2 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2): The impregnation includes vacuum impregnation and pressure impregnation, wherein vacuum impregnation is performed first and then pressure impregnation is performed; The drying and curing temperature is 180° C. to 220° C., and the drying and curing time is 3 to 5 hours; and / or The immersion and drying solidification of each of the at least two slurry dispersions are independently repeated 2 to 4 times.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step (3): The continuous carbon nanotube fiber has a tensile strength greater than 3 GPa, a single filament diameter of 10 μm to 15 μm, a room temperature thermal conductivity of 400 to 600 W / m·K, a breaking elongation of 4% to 6%, or a linear density of 50 tex to 70 tex.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step (4): The particle size of the HfC slurry is 100 nm to 300 nm; The HfC in the HfC slurry is 15 volume % to 25 volume %; and / or The curing temperature is 200° C. to 400° C., and the curing time is 2 hours to 4 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that In step (5): The curing temperature of the polycarbosilane precursor is 200 to 400° C., the curing time is 100 to 360 minutes, the cracking temperature is 800 to 1000° C., and the impregnation and cracking are repeated until the mass increment is less than 1%.

9. A C-CNTF / HfC-SiC ceramic matrix composite material prepared by the method according to any one of claims 1 to 8.

10. The C-CNTF / HfC-SiC ceramic matrix composite material according to claim 9, characterized in that: The content of Z-direction continuous carbon nanotube fibers in the C-CNTF / HfC-SiC ceramic matrix composite material is 5% to 15%; and / or The content of graphene in the C-CNTF / HfC-SiC ceramic-based composite material is 0 volume % to 30 volume %.

Citation Information

Patent Citations

  • Cnt-infused fibers in carbon-carbon composites

    CN102598875A

  • Knittable full-carbon memory storage device, preparation method therefor, and application

    CN105720192A

  • Method for preparing graphene column and carbon nano tube fiber reinforced SiCN composite

    CN108101548A

  • Preparation method of ultrahigh-temperature silicon carbide ceramic-based composite material and ultrahigh-temperature silicon carbide ceramic-based composite material

    CN114163252A

  • Production of oxidation-resistant carbon fiber-reinforced carbon composite material

    JP1994183863A